Haemato-Biochemical Studies in Patients with Ringworm Infections at a Tertiary Care Hospital - Ahmed, Mohammad Nesar Uddin; Rashid-Un-Nabi, Quazi Md; Rahman, Md Saydur; Mahmud, Hasan; Khan, Md Nurul Islam; Nurunnabi, Mohammad (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Ringworm infections, caused by dermatophytes, are communal superficial fungal diseases that exhibit distinct clinical patterns across age and gender groups. Infected patients demonstrated mild normocytic anemia, leukocyte shifts with increased eosinophil and monocytes, altered lipid profiles, elevated inflammatory markers and impaired glycemic control compared to healthy controls. Objective: To evaluate and compare the hematological and biochemical profiles of ringworm-infected patients with healthy controls at a tertiary care hospital. Methods: This case-control study was conducted from April to September 2024 at Kurmitola General Hospital with the collaboration of Department of Physiology, Armed Forces Medical College, Dhaka. It included 250 adults (125 ringworm- infected cases and 125 healthy controls), stratified by age (18–30, 31–45, >45 years) and gender. Socio-demographic data and clinical types of ringworm were recorded. Blood samples were analyzed for hematological parameters and biochemical markers. Results: Tinea cruris (27.2%) was the most prevalent clinical type infection, predominantly affecting younger males, followed by Tinea corporis (25.6%) and Tinea unguium (20.8%) in older females. Infected patients exhibited significantly altered hematological parameters, including mild normocytic anemia, leukopenia with neutropenia, relative eosinophilia and monocytosis, thrombocytopenia and elevated ESR (all p < 0.05). Biochemically, they showed reduced cholesterol and triglyceride levels, elevated ALKP, altered liver and renal markers and higher glycemic indices compared to controls. Conclusion: Despite similar socio-demographic profiles, ringworm infection is akin to consistent hematological and biochemical disturbances including mild anemia, altered immune cells, inflammation, dyslipidemia, liver enzyme shifts, and impaired glucose control emphasizing its broader systemic impact and the need for thorough clinical evaluation. JAFMC Bangladesh, Vol 21, No 2 (December) 2025:17-21